Pengembangan Instrumen Asesmen Berbasis Literasi Numerasi Pada Materi Skala Perbandingan Pada Kelas V SD - Widia Widia; Nyiayu Fahriza Fuadiah; Nora Surmilasari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Numerical literacy is a vital skill in daily life and plays an important role in students' mathematical problem-solving abilities. This study aims to develop an assessment instrument that can measure the numeracy literacy of grade V elementary school students in understanding and applying the concept of comparative scale. This study uses a development method using a 4D development model for the stages of define, design, develop, disseminate The assessment instrument developed consists of various questions designed to test students' understanding of the comparative scale. The trial was carried out on a sample of grade V elementary school students to validate this assessment instrument. The results of the trial show that this assessment instrument has good validity and reliability in measuring students' numeracy literacy skills. This research is expected to contribute to improving mathematics learning in